THE REFORMATION OF MEDICAL ORGANIZATIONS IN OMNIBUS LAW ON HEALTH: SINGLE OR MULTI-BAR - Rikko Hudyono; Suparnyo Suparnyo (UNISSULA, 2023)
The Omnibus Law on Health had been approved which in consequence allow other medical professional organizations to be established as doctors’ right to organize in which may provoke ethical problems. The recent Omnibus Law on Health enabled opportunity for multi-bar organizations; even it was in accordance with single-bar system. This paper aims to review the medical professional organization system in the Omnibus Law on Health which is most in line with the freedom of association and does not reduce the right to health as a human right that must be accepted by the wider community. The author argues that the emergence of several professional organizations as embodiment of doctor’s right may not suitable as it may procure ethical ambiguity. However, the compulsion to join single organization per se was a violation of our Constitution. In this case, we need the highest regulatory and controlling authority from the State to preserve the public interest. The concept of this federal multi-bar association may solve this problem.